As medidas cranianas no diagnóstico das craniossinostoses - José Aloysio da Costa Val Filho (2013)
Craniosynostosis are a group of growth disturbances of the skull, which can result in serious consequences for the child. Early diagnosis provides treatment at the correct time. The head circumference (HC) is usually used as a parameter for its diagnosis, but the HC does not appear to be changed in this disease, leading to incorrect interpretations. The Anteroposterior Distance (APD) and Biauricular Distance (BAD) appear to be more accurate. The aims of this study are to analyze the value of the HC and the ratio of the measures APD to BAD for this diagnosis. We analyzed the data from 129 children who had already undergone an operation for craniosynostosis at the Biocor Instituto, from 2008 to 2010. These data were compared with the normal standards of the population and statistically analyzed to establish their alterations. The HC did not change significantly in craniosynostosis, either as a single group or when considering the subtypes. The APD/BAD ratio changed significantly in the group. The HC does not appear to be useful in the diagnosis of craniosynostosis as an individual parameter. The ratio of the measures APD to BAD appears to help in the diagnosis, as does the relationship of this ratio with the HC.